Emergency management in building based on 3D BIM and GIS technology - Mohd Aizat Saiful Bahrid,; Syed Ahmad Fadhli Syed Abdul Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2022)
An emergency route is a route designed for human use to save themselves from dangerous situations. However, if it is considered trivial, this has unknowingly led to an increase in accidents. The provision of emergency routes on a community scale in indoor areas in terms of time is rarely discussed in emergency evacuation studies. This study aims to investigate the emergency route in the building due to the environmental factors of the closed area and the arrangement of office equipment. The method of this study is divided into two sub-sections, namely data preparation and data analysis process. Demographic data and physical interactions were used as the selection of walking speed criteria while the use of geometric data to see the actual plan route position of the building. 3D building models are built through Revit software and then converted to industry foundation classes format (.IFC) and then to multipatch shapefile (.shp) to be integrated into ArcGIS software. This is intended for the use of the data analysis process that is to build a geometric network model (GNM). GNM is designed to determine the safest and shortest routes by taking into account a variety of obstacles based on the scenario conditions. The findings shows that the evacuation time is influenced by the speed and distance of the route. 80% of the safest route selection takes a long time compared to the shortest route, while 20% is the same distance and time for the shortest and safest route because route selection is the same. The findings able to be used as a reference and guideline to determine the selection of emergency routes, especially in complex buildings.